Polypropylene organoclay nanocomposite - Muhammad Syazwan, Mazlan (2010)
In large exploration of nanotechnology, polymer based nanocomposite have become major area of current scientific research and industrial application. As reported, by 2009, it is estimated the market size of polymer nanocomposite for industrial purposes is about 48 million pounds. Polymer nanocomposite is invented to meet the purpose of improving the properties of the polymer itself such as mechanical properties, thermal properties, conductivity and many more. In this study, pure material of polymer, Polypropylene (PP) and Sodium (Na+) content organoclay with different ratios of PP/Na+ were synthesized by melt intercalation polymerization with the objective of producing polymer nanocomposite with enhanced mechanical properties specifically, tensile and hardness properties. The predispersed master batch of different ratio of PP/Na+ nanocomposite were shaped into a pellet form by using a twin screw extruder before molded into a dog-bone form by hot press machine. The samples are varies by weight percent starting with pure Polypropylene, 1%, 3% and 5% of cloisite Na+. The samples were characterized by Fourier Transform Infrared (FTIR) Spectroscopy, tested mechanically using Universal Testing machine for tensile properties and hardness properties via Brinell Hardness Test. FTIR studies illustrate that Na+ organoclay successfully intercalated into the Polypropylene layer. The resulting composites indicated about 70% increases in the modulus for tensile, compared to pure Polypropylene. In tensile test, a maximum load is applied on the sample until it reaches on its break point. While for hardness test it’s about 24% increases, compared to pure Polypropylene. Hardness was measured on a Rockwell type instrument modified to measure the depth of the unrecovered indentation. A good mixing process and dispersion of Na+ can ensure a high increment of the mechanical properties. Samples also need to be fully dried, so that less bubbles, which affecting the data, can be produced during hot press molding process.